If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + -7) = -9 Reorder the terms: 3(-7 + n) = -9 (-7 * 3 + n * 3) = -9 (-21 + 3n) = -9 Solving -21 + 3n = -9 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 3n = -9 + 21 Combine like terms: -21 + 21 = 0 0 + 3n = -9 + 21 3n = -9 + 21 Combine like terms: -9 + 21 = 12 3n = 12 Divide each side by '3'. n = 4 Simplifying n = 4
| 3x^2+3y^2-6x+12y-9=0 | | 5c-7=c+49 | | 15x=15x+5-5 | | .4b-8=-.2+7 | | 8v-8=10-V | | 8/-3-7=-3 | | 2*(6.8+n)= | | C+49=5c-7 | | -5=-3+2m | | 2x-10+2y=180 | | 3*6p= | | y=sin(7x^2) | | 3+x-9=21 | | 11y+1=4y-9[-4] | | 3+x-9=-21 | | (6v^2)/(9u^3v^2-12vw)=0 | | 5u-26=3u | | 3(5x-x)-3(1-2x)=42 | | x+56=126 | | 13.21+5y=10y-11.79 | | -12x-27=-9x+54 | | k/2=10 | | 6+m=7 | | -12-8x=-7x+16 | | 5v-45=10v-90 | | 2(f-3)-10=7(f+2) | | 7-n=-4n-8 | | lne^3x=27 | | -7+x=33 | | 13=7x-2y | | 0.5(3x+8)=4(1.5x-1.25) | | 4x^2-8y^2=1 |